A constellation of mud volcanoes originated from a buried Arctic mega-slide, Southwestern Barents Sea - Claudio Argentino; Rune Mattingsdal; Tor Eidvin; Sverre Ekrene Ohm; Giuliana Panieri (Scientific Reports)
Abstract Global estimates on the number of submarine mud volcanoes are highly uncertain, as well as their role in the deep-sea biosphere and methane budgets. Here, we report the discovery of ten Arctic mud volcanoes in the Barents Sea (440–480 m depth), where only two had been previously known. The new mud volcanoes form flat-topped mounds on the seafloor and are connected to seismic chimneys rooted within the infilling of a buried Pleistocene mega-slide scar. We suggest informally naming the area the Polaris Mud Volcano Complex. These structures have been active at least since the Late Weichselian deglaciation (< 20 ka), displaying evidence of ongoing methane-rich mud expulsion, i.e. mud pools and flows and chemosynthetic fauna. Finally, we propose a conceptual model for their formation which can be exported to other similar settings. Given the widespread occurrence of mega-slides and associated deposits along (paleo)glaciated continental margins, our findings call for a re-evaluation of mud volcanism potential in such regions.